2018
DOI: 10.1007/s00395-018-0710-1
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetically modified cardiac mesenchymal stromal cells limit myocardial fibrosis and promote functional recovery in a model of chronic ischemic cardiomyopathy

Abstract: Preclinical investigations support the concept that donor cells more oriented towards a cardiovascular phenotype favor repair. In light of this philosophy, we previously identified HDAC1 as a mediator of cardiac mesenchymal cell (CMC) cardiomyogenic lineage commitment and paracrine signaling potency in vitro—suggesting HDAC1 as a potential therapeutically exploitable target to enhance CMC cardiac reparative capacity. In the current study we examined the effects of pharmacologic HDAC1 inhibition, using the benz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 48 publications
0
35
0
Order By: Relevance
“…Recently, mitochondrial elongation factor 1 (MIEF1) was identified as a potential novel mitochondrial division mediator [9]. Higher expression of MIEF1 has been observed in models of brain ischemia reperfusion injury [10] and ultraviolet irradiation-induced epidermal injury [9]. However, the biological role of MIEF1-related mitochondrial division in 5-FU resistance is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, mitochondrial elongation factor 1 (MIEF1) was identified as a potential novel mitochondrial division mediator [9]. Higher expression of MIEF1 has been observed in models of brain ischemia reperfusion injury [10] and ultraviolet irradiation-induced epidermal injury [9]. However, the biological role of MIEF1-related mitochondrial division in 5-FU resistance is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Although cell therapy is a promising and safe approach for the treatment of heart failure (HF) 1 , 2 , the mechanism whereby injected cells improve heart function remains poorly understood. Preclinical studies have shown that improvement of left ventricular (LV) function after cell therapy is associated with increased angiogenesis and reduction of fibrosis and inflammation 1 , 3 7 . It is now well accepted that injected cells do not improve heart function by differentiating into cardiomyocytes and endothelium 1 , 8 12 .…”
Section: Introductionmentioning
confidence: 99%
“…3) SMA expression was lower in hCC than either parental cell, but higher in mouse CCs than the been suggested as the mechanistic basis for cardioprotection using cell therapy 44,45,46 , so the 19 relevance of the secretome from hCCs deserves further detailed analyses to establish a putative 20 role in enhancing survival signaling. The potential contribution of cell fusion to heart regeneration 21 is essentially unexplored despite the established role of cell fusion as a reprogramming mechanism 22 leading to enhanced proliferation and growth rate in differentiated cells 47 .…”
Section: Discussionmentioning
confidence: 94%